Perspectives of ERCC1 in early-stage and advanced cervical cancer: From experiments to clinical applications - Du, Pei; Li, Guangqing; Wu, Lu; Huang, Minger (Frontiers in Immunology, 2023)
Cervical cancer is a public health problem of extensive clinical importance. Excision repair cross-complementation group 1 (ERCC1) was found to be a promising biomarker of cervical cancer over the years, however, no relevant review article has summarized such evidence. In this review, nineteen eligible studies were included for evaluation and data extraction. Based on the data from clinical and experimental studies, ERCC1 plays a key role in the progression of carcinoma of the uterine cervix and the therapeutic response of chemoradiotherapy. The majority of the included studies (13/19, 68%) suggested that ERCC1 played a pro-oncogenic role in both early-stage and advanced cervical cancer and its high expression was found to be associated with the poor survival of the patients. ERCC1 polymorphism analyses demonstrated that ERCC1 might be a useful tool for predicting the risk of cervical cancer and the toxicities that underwent cisplatin treatment. Experimental studies indicated that the biological effects exerted by ERCC1 in cervical cancer might be mediated by its associated genes and affected signaling pathways (i.e., XPF, TUBB3, and p53-EGFR-ERCC1). To move toward clinical applications by targeting ERCC1 in cervical cancer, more clinical, in-vitro, and in-vivo investigations are still warranted in the future.